ENHANCEMENT OF BREAST MILK PRODUCTION THROUGH THE COMBINATION OF OXYTOCIN MASSAGE AND LAVENDER AROMATHERAPY IN POSTPARTUM MOTHERS - Sahriana Sahriana; Jasmawati Jasmawati; Lukman Nulhakim (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Breast milk is the best food for infants as it can fulfill the baby's nutritional needs comprehensively. Breast milk production can increase and decrease, and one of the factors is stimulation of the mammary glands, especially during the first week of lactation. This stimulation can be enhanced through oxytocin massage and lavender aromatherapy, as they stimulate the oxytocin hormone. Objective: To determine the effect of oxytocin massage and lavender aromatherapy on breast milk production in postpartum mothers at Klinik Pratama Triana Nur 2 Sangatta Utara. The research design is a quasi-experimental Pre-test Post-test Design With Control Group. The population of the study is all postpartum mothers who gave birth at Klinik Pratama Triana Nur 2 Sangatta Utara. The sampling technique is consecutive sampling, with a total of 34 participants, 17 in the experimental group and 17 in the control group. The observation of breast milk production is the measurement tool. Data analysis techniques involve the Wilcoxon test and Mann Whitney test. There is a difference in the smoothness of breastfeeding before and after the combination of oxytocin massage and aromatherapy with a p-value of 0.000. There is a difference in breastfeeding smoothness before and after without the combination of oxytocin massage and lavender aromatherapy with a p-value of 0.008. There is an influence of the combination of oxytocin massage and lavender aromatherapy on the improvement of breastfeeding smoothness in postpartum mothers at Klinik Pratama Triana Nur 2 Sangatta Utara with a p-value of 0.003. Discussion: Oxytocin massage and lavender aromatherapy trigger the oxytocin and prolactin hormones to stimulate production due to their relaxation effects. The combination of oxytocin massage and lavender aromatherapy can increase breast milk production.